Saudi Arabia as a Foreign Direct Investment Destination in the GCC: Current Position, Future Prospects, and Policy Imperatives - Alseiari, Hamad Ali Saeed Salem; Aljaeedi, Mohammed Abdullah Ali Amer; Fernandez, Manuel (International Journal of Economics and Financial Issues, 2026)
This study examines the attractiveness of Saudi Arabia as a destination for foreign direct investment (FDI) within the Gulf Cooperation Council (GCC). The study assesses the Kingdom's current position relative to other GCC countries, identifies the main factors affecting investor choices, and proposes policy steps to make Saudi Arabia a more attractive FDI destination. The study uses a comparative research design that covers multiple countries and is based on Dunning's eclectic OLI theory and location-specific factors. Secondary data for 2020–2024 were collected from the World Investment Report, World Bank, IMF, and other international sources. The findings show that Saudi Arabia is consistently ranked second among GCC countries in FDI inflows, with total inflows of about USD 95.2 billion during the study period. This reflects the positive effect of the Vision 2030 reform programme. The Kingdom is strong in market size, economic growth potential, and digital and innovation development. However, it still lags behind the UAE, the region's top FDI destination, in several key areas of institutional quality and competitiveness. The study concludes with policy recommendations on regulatory reform, talent attraction, sectoral diversification, and digital ecosystem development to help reduce this gap and make Saudi Arabia the top FDI destination in the GCC in the near future.